Time Trends in Cardiovascular Event Incidence in New‐Onset Type 2 Diabetes: A Population‐Based Cohort Study From Germany - Theresia Sarabhai; Karel Kostev (Journal of Diabetes)
ABSTRACT Background Events of cardiovascular disease (CVD) remain a critical concern in patients with Type 2 diabetes mellitus (T2D). Over 17 years, this study analyzed time changes in the 5‐year incidence of myocardial infarction (MI), chronic coronary heart disease (CHD), transient ischemic attack (TIA), and ischemic stroke (IS). Methods This retrospective cohort study was conducted using the Disease Analyzer database, including patients aged ≥ 18 years with at least 12 months of no prior CVD with new‐onset T2D in 2001–2006 (n = 10 162) and in 2013–2018 (n = 30 486), matched 1:3 by age and sex. Kaplan–Meier survival analysis estimated the 5‐year cumulative incidence of the outcomes. Multivariable Cox regression models assessed temporal changes, adjusted for comorbidities. Results The incidence of CHD and TIA significantly declined in 2013–2018 compared to 2001–2006, with HRs of 0.68 (95% CI: 0.63–0.73; p < 0.001) and 0.63 (95% CI: 0.52–0.76; p < 0.001), respectively. Reductions were more pronounced in women and older patients. Surprisingly, MI incidence showed only a trend of reduction (HR: 0.82; 95% CI: 0.68–0.99; p = 0.045) and IS incidence was not different (HR: 0.97; 95% CI: 0.85–1.12; p = 0.722) between time periods. Conclusions This study is the first to report time trends in CVD incidence in new‐onset T2D in Germany. From 2001 to 2018, the 5‐year incidence of CHD and TIA decreased in new‐onset T2D, reflecting demographic‐specific advancements in diabetes and cardiovascular care. However, the stable incidence of IS and MI underscores a persistent challenge in prevention strategies in patients with prediabetes and T2D.